Smart fixes for your printing, e-mail, and audio hassles. - Bass, Steve
Save printer ink, handle leftover Registry junk, and defeat a common Outlook annoyance.
Keywords: Ink-jet printers; Microsoft Outlook; Class IDs; CLSIDs